THE INFLUENCE OF PRODUCT DEVELOPMENT AND MARKETING COMMUNICATION ON INCREASING SALES VOLUME IN PT. GLOBAL UGGUL MANDIRI – PAXEL HEAD OFFICE, JAKARTA - Martha Ayerza Esra (International Journal of Social Science, 2023)
The increase in sales volume is very important for a company development. Companies use all techniques to increase sales volume, from creating new products that meet consumer needs to marketing communications. With direct or indirect marketing techniques to introduce products that are owned by the company. In the current era, there are many ways to conduct marketing communications, one of which is with technology-based social media. This research was conducted using survey data methods, based on product development data, marketing techniques to the desired result in the form of volume increase.